Perancangan Karakter Animasi 2D Filosofi Pakaian Pernikahan Batak Angkola - Timothy Karsten Anggiva; Ratih Pertiwi (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Indonesia is a unitary state in the form of a Republic with its own government, territory, people , and international recognition. Indonesia consists of 38 provinces and has more than 1,300 ethnic groups with diverse tribes, cultures, and traditions spread across various regions. One of the ethnic groups in Indonesia is the Batak tribe. This journal will discuss the Batak Angkola culture and the Batak Angkola Traditional Wedding Attire. This traditional wedding attire represents harmony, respect for ancestors, and a symbol of responsibility in household life. Thus, the Angkola traditional wedding attire is not just traditional clothing, but also a cultural educational medium that can be passed down to future generations.